Tradisi Makulkulan Dalam Perkawinan Di Desa Adat Sidayu Tojan Desa Takmung Kecamatan Banjarangkan Kecamatan Klungkung - Ni Made Anggreni (Jurnal Penelitian Agama Hindu, 2020)
Kulkul has a very complex meaning as a communication medium seen from the horizontal dimension having a communication function in aspects of community life, meaning that kulkul is a medium for communication to jointly create open lines of communication in interactions between community members. Whereas vertically kulkul has a meaning / function related to religious rituals as a link between the implementation of the yajña ceremony and Ida Sang Hyang Widhi Wasa. In the development and modernization of civilization, the Sidayu Tojan Traditional Village community can still maintain its traditional tools such as the kulkul in its relation as an aspect of communication to society. The theories used in this research are Theory of Religion and Symbolic Interactionism Theory. Determination of informants in this study using purposive sampling technique. Data collection techniques used in this study were observation, interviews, and literature study. Data analysis, carried out by qualitative descriptive. Kulkul is functioned for rituals and social life, so it is very interesting to be appointed in a study. This will also be very useful in exploring the various values ​​embedded in the great thinking framework of the community's predecessors who sparked the idea of ​​making kulkul as a means of communication which functions very important in society in Bali.